POLITICS AND BUSINESS DISPUTES: THE ROLE OF LAWYERS IN FOREIGN BUSINESS DISPUTING IN KAZAKHSTAN - Altynbayeva, Zhadyra (Nazarbayev University School of Sciences and Humanities, 2018)
The scholarship on business disputes settlement in non-democracies while emphasizing the importance of lawyers cannot explain why and how they shape the businesses disputing behavior. I argue that lawyers’ case choices influence the business dispute settlement choices. Lawyers in non-democracies appear to be very important intermediaries for foreign businesses due to their informer role and dispute resolution services providing. Lawyers inform foreign businesses about the contextual peculiarities of business disputing in Kazakhstan, such as the importance of political actors. Using various data sources like legal documents, media stories, interview with lawyers and composing dataset of foreign businesses disputes against Kazakhstan, I find that when the political actors are parties to the dispute lawyers are unlikely to take the case and advise foreign businesses to settle the dispute in foreign arbitration tribunals, if that condition is supported by 100% loss of investments. The reason for such decisions lies in the awareness of the lawyers about the control political actors possess over all dispute settlement fora like arbitration, court, and negotiation. Another important factor appears to be the profit interests of the lawyers, which is comprised of time vs. money calculations and are lower in disputes with political actors. My study also reveals variation among lawyers’ perception of reputation, that determines their choices in handling the disputes.....
САЯСАТ ЖӘНЕ БИЗНЕС ДАУЛАР: ҚАЗАҚСТАНДАҒЫ ШЕТЕЛДІК БИЗНЕС ДАУЛАРДЫ ШЕШУДЕ ҚҰҚЫҚШЫЛАРДЫҢ РӨЛІ
ПОЛИТИКА И БИЗНЕС СПОРЫ: РОЛЬ ЮРИСТОВ В РАЗРЕШЕНИИ ИНОСТРАННЫХ БИЗНЕС СПОРОВ В КАЗАХСТАНЕ
Keywords: politics and business disputes; lawyers